Correlation of Neutrophil-Lymphocyte Ratio, Monocyte-Lymphocyte Ratio, and Platelet-Lymphocyte Ratio with Stunting in Children - Stanpo, Gwyneth Trixie; Notopuro, Paulus Budiono; Widjaja, Nur Aisiyah (Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Globally, stunting affected approximately 148 million children under five in 2022. Chronic infection contributes to stunting through immune hyperactivation and excessive cytokine release. Since anthropometric assessments are prone to errors and may not accurately reflect the underlying inflammatory status, common systemic inflammatory markers, such as the Neutrophil-Lymphocyte Ratio (NLR), Monocyte-Lymphocyte Ratio (MLR), and Platelet-Lymphocyte Ratio (PLR), can serve as alternatives. These markers are simple, affordable, and accessible in every health center.Objective: To analyze the correlation of NLR, MLR, and PLR with stunting.Methods: A cross-sectional study involving pediatric patients aged 1-5 years from the Nutrition and Metabolic Outpatient Clinic of Dr. Soetomo Regional Hospital in Surabaya from 2022 to 2023. Forty-one samples met the inclusion and exclusion criteria. Data on NLR, PLR, MLR, and other hematological variables were obtained from the patients' hematology profiles. Group differences, correlations, and diagnostic performance were analyzed using Kruskal–Wallis, Spearman, and ROC methods, respectively.Results: Forty-one subjects were obtained and divided into three groups: 21 (51.2%) normal, 10 (24.4%) stunted, and 10 (24.4%) severely stunted. RBC and lymphocytes significantly increased in normal patients, whereas neutrophils, platelets, NLR, MLR, and PLR significantly increased in severely stunted patients. NLR, MLR, and PLR differed significantly between normal and stunted children (p =<0.001; p =0.002; and p =<0.001, respectively) and showed positive correlations between the NLR (p =<0.001; r =0.687), MLR (p =<0.001; r =0.558), and PLR (p =<0.001; r =0.784) with stunting. At cutoff values of 0.844 (NLR), 88.527 (PLR), and 0.174 (MLR), their AUCs were 0.90, 0.95, and 0.82, with sensitivities of 75%, 80%, and 60%, respectively.Conclusion: NLR, MLR, and PLR significantly differ among normal, stunted, and severely stunted children, showing positive associations with stunting. These markers, particularly PLR, may serve as a practical screening tool, warranting further validation through larger studies.